3
$\begingroup$

I am trying to write the product of two stretched exponentials as another stretched exponential function. For example,

$ f(t) = \exp[-(t/\tau_1)^{\beta_1}]$ and $g(t) = \exp[-(t/\tau_2)^{\beta_2}]$

Now, can a function $h(t) = f(t)g(t)$ be also described with a stretched exponential like,

$h(t) = \exp[-(t/\tau)^{\beta}]$

where $\beta$ is related to $\beta_1, \beta_2$ (likewise for $\tau$).

An attempt when one of them is exponential, $\beta_2 = 1$

One can write stretched exponential as a distribution of single exponentials as,

$$ f(t) = \exp[-(t/\tau_1)^{\beta_1}] = \int_0^\infty ds\; P(s,\beta_1)\exp\{-s\frac{t}{\tau_1}\} $$

$$ g(t) = \exp[-t/\tau_2] = \int_0^\infty ds' \; \delta(s'-1)\exp[-s'\frac{t}{\tau_2}] $$

then $h(t)$ can be written as a double integral,

$$ h(t) = \int_0^\infty ds\int_0^\infty ds' \; P(s,\beta_1) \delta(s'-1) \exp\bigg[-s'\frac{t}{\tau_2}-s\frac{t}{\tau_1}\bigg] $$

defining a new set of variables,

$$ \frac{s}{\tau_1} = \frac{a+b}{2\tau}; \qquad \qquad \frac{s'}{\tau_2} = \frac{a-b}{2\tau} $$

with few algebraic manipulations, one obtains $$ h(t) = - \int_0^\infty da \;P\bigg[\frac{a}{2}\bigg(1+\frac{\tau_1}{\tau}\bigg)-\frac{\tau_1}{\tau_2},\beta_1\bigg] \exp[-a \frac{t}{\tau}] $$

which equivalent to saying $h(t)$ is also a stretched exponential with different parameters.

But if I did few more transformations, I could also end up with the following expression that, $$ h(t) = -\int_0^\infty da' \;P\bigg[a'-\frac{\tau_1}{\tau_2},\beta_1\bigg] \exp[-a' \frac{t}{\tau_1}] $$

which just means that the probability distribution is shifted by a constant $(\tau_1/\tau_2)$ but with same stretching exponent $\beta$. Can this also be considered as a stretched exponential?

$\endgroup$
3
+50
$\begingroup$

Taking logarithm of everything your question becomes:

If $ \ln f(t) = -(t/\tau_1)^{\beta_1}$ and $\ln g(t) = -(t/\tau_2)^{\beta_2} $, can the function $\ln h(t) = \ln f(t)+ \ln g(t)$ be also described with a log of stretched exponential, i.e. $\ln h(t) = -(t/\tau)^{\beta}$.

This is false, since the sum $-(t/\tau_1)^{\beta_1} -(t/\tau_2)^{\beta_2} $ in question is not homogeneous in $t$ unless $\beta_1=\beta_2$.

Further explanation about homogeneity: A function is homogeneous of degree $\beta$ if $f(kt)=k^{\beta}f(t)$ for any $k>0$. Clearly logarithm of stretched exponential, being $-(t/\tau)^{\beta}$ is homogeneous of degree $\beta$.

However, I claim that unless $\beta_1=\beta_2$ the function $u(t)=-(t/\tau_1)^{\beta_1} -(t/\tau_2)^{\beta_2} $ is not homogeneous of any degree, essentially because it has wrong scaling behavior, which is easiest to see for very large or very small $t$ (and so not being homogeneous it can not be logarithm of a stretched exponential). Here is a formal proof:

We will actually show that $u(t)$ restricted to positive inputs $t>0$ is not homogeneous. In fact on positive $t$ we have for any non-zero homogeneous function $f(t)$ the formula

$$f(t)=f(t\times 1)=t^\beta f(1)=Ct^\beta$$

So $f(t)/t^\beta=C$ is constant, and in particular

$$\lim_{t\to 0+} f(t)/t^\beta = \lim_{t\to +\infty} f(t)/t^\beta=C$$

which is finite and must be non-zero for non-zero $f(t)$.

Without loss of generality suppose $\beta_1>\beta_2$. Write $$ u(t)/t^{\beta}= C_1 t^{\beta_1-\beta}+C_2t^{\beta_2-\beta}$$

with negative $C_1$ and $C_2$.

Since $\lim_{t\to +\infty} t^a$ is finite and nonzero only if $a=0$, $\lim_{t\to +\infty} u(t)/t^{\beta}$ is finite and non-zero if and only if $\beta =\beta_1$. Similarly, $\lim_{t\to 0+} u(t)/t^{\beta}$ is finite and non-zero if and only if $\beta =\beta_2$. Since we can not have $\beta$ equal to both of them, $u(t)$ is not homogeneous.

$\endgroup$
  • $\begingroup$ It's raised to the power of $\beta$ outside the - sign. But if the sum is not homogenous, is it impossible to write it as an exponent of any real values of $\tau, \beta$. $\endgroup$ – user35952 Apr 3 '18 at 9:38
  • $\begingroup$ Is it possible to solve for $\beta = \beta(\beta_1,\beta_2,\tau_1,\tau_2)$ and $\tau = \tau(\beta_1,\beta_2,\tau_1,\tau_2)$? $\endgroup$ – user35952 Apr 3 '18 at 11:58
  • $\begingroup$ I have corrected the sign; no, it is not possible to solve for $\beta$, no $\beta$ will work -- see the more detailed explanation in the updated answer. $\endgroup$ – Max Apr 3 '18 at 17:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.